Fractionation, Characterization and Evaluation of Biocidal Potential of Active Principles of Leaves of Vitex Negundo Linn. - Kaushik, R.D.; Kumar, Anil; Arora, Charu (Asian Journal of Chemistry, 2010)
Three chemical compounds, n-pentatriacontane, p-hydroxybenzoic acid and 5-hydroxyisophthalic acid have been isolated and characterized on fractionation of hexane and methanol extracts of leaves of Vitex negurndo L. Presence of n-pentatriacontane in the leaf extracts of this plant. The antimicrobial activities of the separated fractions against fungal pathogens like Mycogone perniciosa and Rhizoctonia s~lani and six bacteria Bacillus megatrium, Escherichia coli, Pseudomonas fluoresence, Sarcina lutea, Staphylococcus spp. and Xanthomonas spp. have been reported.